The Efficiency Analysis of Motorcycle Versus Public Transportation: A Case of Cipinang - Tebet Area Route - Rara Salsa Nadillah; Andri Irfan Rifai; Susanty Handayani (Indonesian Journal of Multidisciplinary Science, 2022)
Public transportation modes are one of the essential means of transportation and must be developed. However, today the phenomenon that exists, the selection of motorcycles, is more interesting than the use of public transport. This paper aims to examine how efficient motorcycles compare to public transportation. The research method was a questionnaire distributed to 100 respondents and interviews with Cipinang – Tebet (MT. Haryono). Data analysis is carried out using the Importance Performance Analysis method with the help of the Microsoft Excel application. The results showed that the importance-performance analysis was quite good. It was seen that the average importance level was 3.99, the satisfaction level was 3.56, and the GAP was -0.44. The highest GAP occurs in the Comport Capital parameter of -0.59. Meanwhile, based on the results of interviews shows that travelers prefer to use motorbikes instead of public transportation due to the mileage, travel time, and costs incurred.